2002
DOI: 10.1183/09031936.02.02562001
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related effect of inhaled fluticasone on allergen-induced airway changes in rats

Abstract: To examine whether fluticasone propionate (FP) dose-dependently inhibits inflammatory as well as structural changes, Brown Norway rats were sensitised to ovalbumin (OA) on day 0 and 7. From day 14-28, rats were exposed to aerosolised OA (1%) or phosphate buffered saline every 2 days. Thirty minutes before each allergen exposure, animals were pre-treated with aerosolised placebo or FP (0.1, 1 or 10 mg) or prednisolone 3 mg?kg -1 i.p.At day 29, 0.1 mg FP had no measurable effect, either on inflammatory or struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
(36 reference statements)
2
22
0
Order By: Relevance
“…This finding is consistent with previous reports in which ICS treatment reduced AHR when assessments were made immediately following exposure to allergen in both animals [21,37] and humans [29][30][31]. Furthermore, the present authors reported that inhibition of immune-mediated events attenuates AHR [32][33][34].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with previous reports in which ICS treatment reduced AHR when assessments were made immediately following exposure to allergen in both animals [21,37] and humans [29][30][31]. Furthermore, the present authors reported that inhibition of immune-mediated events attenuates AHR [32][33][34].…”
Section: Discussionsupporting
confidence: 83%
“…41 to attenuate airway remodeling and AHR noted with longer treatment. 31 The observations by Sont et al 30 and Ward et al, 31 as well as others (Table I) [32][33][34][35][36][37][38][44][45][46] suggest that the corticosteroid dose and its duration of administration are important considerations when evaluating the effects of treatment on remodeling. These studies also suggest that some aspects of remodeling might be reversible and that current treatment end points (ie, symptoms alone) might not be fully informative on what approaches are needed to modify airway remodeling.…”
Section: Reticular Basement Membrane Thickeningmentioning
confidence: 90%
“…These results agree with previous studies. 41,[49][50][51][52] In the current study, the monotherapies showed modest non-significant decreases in AHR, while the combination groups showed significant decreases in AHR at MCh concentrations of 25 and 50 (mg/ml). These two doses of MCh could be clinically relevant because maximum doses of 16, 25, and 32 mg/ml are commonly used in various pulmonary functions testing laboratories.…”
Section: Discussionmentioning
confidence: 82%